2007
DOI: 10.3386/w13085
|View full text |Cite
|
Sign up to set email alerts
|

Americans Do I.T. Better: US Multinationals and the Productivity Miracle

Abstract: The US has experienced a sustained increase in productivity growth since the mid-1990s, particularly in sectors that intensively use information technologies (IT). This has not occurred in Europe. If the US "productivity miracle" is due to a natural advantage of being located in the US then we would not expect to see any evidence of it for US establishments located abroad. This paper shows in fact that US multinationals operating in the UK do have higher productivity than non-US multinationals in the UK, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
118
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(133 citation statements)
references
References 13 publications
12
118
0
3
Order By: Relevance
“…The conclusions from growth accounting now receive confirmation from micro studies: see e.g. Brynjolfsson et al (2002), Brynjolfsson and Hitt (2003), Bloom et al (2007), and Draca et al (2006).…”
Section: The Importance Of Ictmentioning
confidence: 59%
“…The conclusions from growth accounting now receive confirmation from micro studies: see e.g. Brynjolfsson et al (2002), Brynjolfsson and Hitt (2003), Bloom et al (2007), and Draca et al (2006).…”
Section: The Importance Of Ictmentioning
confidence: 59%
“…However, substantial variation exists in the returns to IT across firms (Brynjolfsson and Hitt 1995). A leading explanation for this variation is that firms with higher returns also adopt complementary organizational practices that produce productivity and performance premiums (Bresnahan, Brynjolfsson and Hitt, 2002;Caroli and Van Reenen 2002;Aral and Weill 2007;Bloom, Sadun and Van Reenen 2008). For instance, financial markets disproportionately reward firms that invest in IT when they have also made appropriate organizational investments (Brynjolfsson, Hitt, and Yang, 2002).…”
Section: Information Technology and Organizational Complementaritiesmentioning
confidence: 99%
“…With a highly skilled workforce that can efficiently use information technology, firms can achieve higher productivity through increased efficiency and customization as line workers are empowered with more decision rights (Bresnahan, Brynjolfsson and Hitt 2002;Caroli and Van Reenen 2002). Furthermore, IT and organizational investments such as those in innovative people management practices can help explain why the US experienced sustained increases in productivity growth in the last decade while Europe has not (Bloom, Sadun and Van Reenen 2008).…”
Section: Information Technology and Organizational Complementaritiesmentioning
confidence: 99%
“…Today information technology (IT) has been able to assist companies in improving operations and more productive Hitt, 1996, 2003;Bloom et al, 2012). On the other hand some researchers have found that IT it weakens the natural value of an IT that are innovative (Hobijn and Jovanovic, 2001;Gârleanu et al, 2012a, b;Bartelsman, 2013;Papanikolaou, 2013, 2014).…”
Section: Introductionmentioning
confidence: 99%